Evaluation of Predictors for Severity of Dengue Fever at the Beginning of the Disease (Medical Forum Monthly, 2024)
Objective: To evaluate the predictors of severity of dengue at the beginning of the diseaseStudy Design: Prospective and Observational studyPlace and Duration of study: This study was conducted at Shan General Hospital and Trauma and General Hospital from July 2010 to 1st October 2011.Patients and Methods: The study was conducted on all patients who were admitted and confirmed to have dengue fever after positive serology on day VI. There was pre-assigned protocol and every predictive marker was given one point.Results: Patients who had ≥ 4 points at the time of presentation had more severe illness and developed more severe complications rather than those who had ≤ 2 points.Conclusion: Dengue fever is becoming a major health problem. Predictive markers for severity of illness may help in detection of complication and its management.